Adipofascial anterolateral thigh free flap in hypopharyngeal and oropharyngeal reconstruction. Issue 6 (19th January 2022) - Xu, Feng; Deng, Di; Li, Baofei; Li, Linke; Liu, Jifeng; Li, Bo; Liu, Jun; Chen, Fei
Abstract: Background: The anterolateral thigh (ALT) flap is a popular choice for head and neck reconstruction surgery, but its ungainly thickness makes it of limited value in some intracavitary reconstructions. The ALT adipofascial flap is an improved flap without skin or muscle. Here, we seek to further illustrate the ALT adipofascial flap as an alternate method of hypopharyngeal and oropharyngeal reconstruction in head and neck. Methods: A retrospective review of 9 patients (7 men, 2 women) ranging from 28 to 67 years (mean age, 53.1 years) who underwent reconstruction with the ALT adipofascial flap after hypopharyngeal carcinoma (4 patients) or oropharyngeal carcinoma (5 patients) resections from August 2018 to December 2019 was performed. Surgical outcomes and functional resoration were assessed. Results: The size of the flaps ranged from 6 × 4 cm 2 to 6 × 12 cm 2 . The average flap thickness was 0.14 cm (range, 0.1–0.2 cm) and the average pedicle length was 9.8 cm (range, 7–12 cm). The postoperative course was uneventful in eight patients. Reconstruction was successful in all cases during 7–23 months of follow‐up (mean time, 14.3 months). All patients resumed oral feeding for 2–8 weeks (mean time, 4.9 weeks) and the tracheal cannula was successfully removed 0.5–4 months postsurgery (mean time, 2.4 months). Conclusion: The ALT adipofascial flap is a viable choice for hypopharyngeal and oropharyngeal reconstructions and is thinner than the ALT flap. It could be harvested as a single‐pedicled double‐island flap for complex defect reconstruction.